B-Universal multi purpose bottle / Nur Hamisha Adriana … [et al.] - -, Nur Hamisha Adriana; -, Nur Musfirah; -, Norfadillah; -, Muhammad Syahir Irfan; -, Muhammad Aleef Haikal; -, Muhammad Fairuz (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
B-Universal has come up with the new product concept which is a Multi-Purpose bottle based on the normal and thermos water bottle. The multi-purpose bottle is split with two sides which consists of a hot and cold-water section. The design is more like a smart-split bottle. Since we live in modern society, the bottle is suitable for every generation with such a numerous lifestyle. Hence, the bottle is suitable for the younger and older to use in daily life and suit everyone’s taste. For the purpose of this new product, there are four aims. Firstly, this bottle keeps water hot and cold at the same time. Secondly, this bottle is user friendly to use. For instance, for athletes and travelers for them to have enough water supply with high durability. Thirdly, it is also portable and lightweight which makes it simple to use. Finally, for moms with babies this bottle can help with a complete water supply from which to make formula milk when going outside. The bottle is divided into two parts to maintain the ice cold-water and avoid the water to quickly defrost and maintain the hot water for more than12hours. Therefore, the water will not turn to room temperature. With an affordable and reasonable price of RM75, this bottle can give satisfaction to the user who purchases and uses this product and is able for us to keep the price sustainable in the market.